Architectural examination on Feng Shui Bedroom - Chen, Wang; Hong, Wan Thing; Abdul-Rahman, Hamzah (Open House International Association, 2018)
Bedroom Feng Shui practices have been criticized as myth over the years but in fact having its scientific origin that is not purely superstitious. This paper aims to examine whether the architects' design practice for bedroom interior arrangement is concurring with the recommended bedroom Feng Shui practices. The study has successfully interviewed 16 architects from diverse backgrounds to avoid bias, seeking their design perspectives in bedroom interior configuration. Subsequently, the interviewees submitted sketches of ideal bedroom layout based on their expertise, with pre-set requirements. Data from semi-structured interviews were analyzed using mixed method approach. In agreement with our expectations, majority of the interviewees have matching thoughts that "bed arrangement" is the primary consideration in bedroom interior configuration. Most of the design outputs were highly attached to favorable Feng Shui conditions. The overall findings implied that bedroom Feng Shui is not merely superstitious but most components are practical design references for architects from diverse backgrounds.